Integrating building code to microbial count studies in urban built spaces with ventilation and human presence: a model - Ma. Beatrice D. Villoria; Vina B. Argayosa; Angelo D. Rosalinas; Daniel Nichol R. Valerio; Christian Lyle La Madrid; Michael Xavier N. Ticzon (Frontiers in Built Environment)
In this work, a conceptual framework is proposed for translating microbial research into usable design tools in an urban built environment. This study on Microbiomes of the Built Environment (MoBE), specifically the cultivable microbial count, incorporates building code and built environment design factors applied in the Philippine setting. The National Building Code of the Philippines with focus on minimum habitable room specifications was used to provide basis for the framework process. Human presence and ventilation were used as parameters to produce data that can be used as design tools. Using passive air sampling, the three experiments were conducted within Metro Manila according to the proposed framework. The first experiment using settle plates of culture media in the morning and afternoon seeks to understand how bacterial and fungal counts are affected in a naturally ventilated and in a non-ventilated room. The second and third experiments were done to test the effects of different window sizes and the number of humans on bacterial count, respectively. Results showed higher bacterial count in the room with natural ventilation compared to the room with no ventilation. The use of different window sizes did not show significant difference in counts with the number replicates used but as the number of humans in the area increased, the bacterial counts also increased. Data produced in the preliminary experiments were used to conceptually design a space in this paper. The authors suggest that this building-code inspired framework be used as a guide for MoBE studies as a starting point and be further developed to understand and eventually produce healthier built environments.